A Study on Psychological Well-Being and Kesejahteraan among IIUM Malaysian Postgraduate Students - Shamsul Azman, Sarah; Abd Karim, Aishah Hanim; Ismail, Nik Ahmad Hisham (IIUM Journal of Educational Studies, 2023)
The study aimed to investigate the two elements of well-being, namely psychological well-being, and the threats towards well-being to ascertain the relationship between psychological well-being and the Sejahtera of Malaysian postgraduate students at International Islamic University Malaysia (IIUM). While mental health issues among university students have been abundantly researched, only a few studies have focused on psychological well-being. Employing the Carol Ryff’s Psychological Well-Being (PWB) questionnaire, data were collected from 283 IIUM Malaysian postgraduate students. Descriptive analysis, independent t-test and analysis of variance (ANOVA) were used to analyse the data. The results revealed that Malaysian postgraduate students’ education at IIUM are doing well in terms of their psychological well-being (autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance). The relationship between psychological well-being and student’s Sejahtera showed that these students were able to manage their psychological well-being, including personal matters, stress, time management, acceptance of emotions and thoughts. In conclusion, the six factors of psychological well-being were able to support and balance the threats, at the same time helping the students to achieve Sejahtera.